BZT305- Vertebrate Zoology (Zoologi Vertebrata) - PPSKJ, Pusat Pengajian Sains Kajihayat (Pusat Pengajian Sains Kajihayat, 2024)
First Semester Examination 2023/2024 Academic Session . February 2024 BZT305- Vertebrate Zoology (Zoo/ogi Vertebrata) Duration : 2 hours (Masa : 2 jam)